2002
DOI: 10.1016/s0022-2275(20)30473-9
|View full text |Cite
|
Sign up to set email alerts
|

Dietary long-chain n-3 PUFAs increase LPL gene expression in adipose tissue of subjects with an atherogenic lipoprotein phenotype

Abstract: We sought to test the hypothesis that dietary longchain n-3 PUFA (LC n-3 PUFA) in fish oil stimulate the gene expression of lipoprotein lipase (LPL) in human adipose tissue (AT). In a randomized, double blind, placebo-controlled, cross-over study, 51 male subjects expressing an atherogenic lipoprotein phenotype (ALP) had their diets supplemented with fish oil for 6 weeks. As we previously reported for this group, supplementation with LC n-3 PUFA produced a decrease in fasting plasma triglyceride (TG) ( ؊ 35%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(12 citation statements)
references
References 38 publications
1
9
0
2
Order By: Relevance
“…This trend was consistent with findings obtained in orange-spotted grouper and mammals [5,55]. Past study showed that n-3 PUFA in fish oil increase lpl expression in adipose tissue of mammals [56], which might be part of the reason for the lower lpl expression in turbot fed the L171.2 diet, but further research is required. Studies have shown that activation of pparα could promote fatty acid β-oxidation by promoting the expression of cpt1, which is the rate-limiting enzyme for fatty acid oxidation [57,58].…”
Section: Discussionsupporting
confidence: 91%
“…This trend was consistent with findings obtained in orange-spotted grouper and mammals [5,55]. Past study showed that n-3 PUFA in fish oil increase lpl expression in adipose tissue of mammals [56], which might be part of the reason for the lower lpl expression in turbot fed the L171.2 diet, but further research is required. Studies have shown that activation of pparα could promote fatty acid β-oxidation by promoting the expression of cpt1, which is the rate-limiting enzyme for fatty acid oxidation [57,58].…”
Section: Discussionsupporting
confidence: 91%
“…The total TG‐lowering effects of fenofibrate as well as fish oil are well documented [ 8,19 ] and are in line with what was previously reported in the same study population. [ 20 ] The effects of fenofibrate have previously been ascribed to an increased TG clearance by activation of lipoprotein lipase via PPAR‐mediated decrease of APOC3 gene expression, [ 21–24 ] and a decreased TG production and secretion from the liver via upregulation of fatty acid beta oxidation via PPAR activation. [ 25 ] The TG‐lowering effects of fish oil, on the other hand, have previously, at least partly, been ascribed to a reduction of ApoB synthase in the liver, thereby impairing VLDL assembly and secretion.…”
Section: Discussionmentioning
confidence: 99%
“…LPL harbors a PPRE in its promoter region, which evidence suggests is responsive to both dietary and pharmacological agents. 31,32 We hypothesize that for subjects carrying at least one copy of the rs13702 minor C, elevated dietary PUFA intake will further increase LPL levels in the absence of regulatory inhibition by miR-410. However, for those individuals homozygous for the rs13702 major T allele, any increase in LPL resulting from PUFA stimulation may be subject to translational inhibition by miR-410, resulting in a less robust response to dietary PUFA (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…The LPL promoter contains a functional peroxisome proliferator response element (PPRE), and PPREs are responsive to fatty acids. 31,32 Therefore, we hypothesized that the proposed allele-specific regulatory effect of rs13702 may differentially regulate LPL levels in response to dietary fat. To examine this hypothesis, we meta-analyzed our cohort data for statistically significant interactions between rs13702 and dietary fatty acids in modulation of lipid phenotypes.…”
Section: Introductionmentioning
confidence: 99%